Legal and Cultural Implications of Personal Data Protection in the Era of Global Digital Society - Mustafa; Slamet Sarwo Edy (Jurnal Hukum Caraka Justitia, 2026)
The Indonesian government must safeguard, guarantee, and protect people's personal data from being hacked by irresponsible parties. This research examines laws regarding legal protection efforts for the right to personal data privacy from hacking crimes. However, this is not enough to guarantee protection against hacking of people's personal data in cyberspace, which is increasingly common nowadays, very broad, covering analysis of legal frameworks, comparison of international regulations, socio-cultural impacts, and challenges of cross-border implementation. The results of the research conclude that law enforcement regarding the protection of the right to privacy of personal data is not yet fully optimal, judging from the number of cases that have occurred recently. The legal pillars already exist, and our collective hope is that law enforcement can be carried out optimally, so that there are no more cases of hacking into someone's data, which could cause losses in the future. Apart from that, there is legal uncertainty regarding the protection of personal data, because Indonesia currently does not have legal instruments and technology that can detect data theft in the digital era. The author's view is that legal instruments for protecting privacy and personal data in the era of global digitalization must at least meet 3 criteria: (1) protecting privacy and personal data as a human right, (2) it is an element that binds individuals and society in all fields, including law, economics, and politics. and (3) international in nature.